2008
DOI: 10.1002/path.2307
|View full text |Cite
|
Sign up to set email alerts
|

Side populations of gastrointestinal cancers are not enriched in stem cells

Abstract: The side population (SP) phenotype, defined as the reserpine-blockable ability to efflux the nucleic acid dye Hoechst 33342, has been claimed to be enriched for stem cells in several human normal tissues, cancers and cell lines, and thus may be useful for the identification and isolation of cancer stem cells. We demonstrated the presence of SP fractions in all of seven tested gastrointestinal cancer cell lines. Four cell lines were selected (HT29, HGT101, Caco2 and HRA19a1.1) for detailed phenotypic and behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
70
0
2

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(79 citation statements)
references
References 33 publications
7
70
0
2
Order By: Relevance
“…Burkert et al 15 found that SP cells derived from gastrointestinal cancers cell lines HT29, HGT101, Caco2, and HRA19a1.1 were not enriched with a CSC/TIC population. In the present study, we were able to isolate SP cells from all six colon cancer cell lines studied (SW480, HT29, HCT15, KM12LM, Lovo, and Colo320).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Burkert et al 15 found that SP cells derived from gastrointestinal cancers cell lines HT29, HGT101, Caco2, and HRA19a1.1 were not enriched with a CSC/TIC population. In the present study, we were able to isolate SP cells from all six colon cancer cell lines studied (SW480, HT29, HCT15, KM12LM, Lovo, and Colo320).…”
Section: Discussionmentioning
confidence: 99%
“…All these SP cells were specifically inhibited by verapamil, as has been shown previously, 14 suggesting that these SP cells were specific for ABC transporter expression. Because previous studies showed that some colon cancer SP cells were not enriched with a CSC/TIC population, 15 it was essential to confirm the presence of CSCs/TICs in SP cells for further analysis. We inoculated these SP cells subcutaneously into the back of immunodeficient NOD/SCID mice using serial dilution.…”
Section: Isolation Of Colon Cscs/tics As Sp Cellsmentioning
confidence: 99%
“…The ratios of SP cells in Caki1, SMKTR2, and SMKTR3 cells were too low for further analysis, and we therefore used ACHN and RenCa in the following experiments. It has been shown that SP cells were not enriched with CSCs/ CICs in some types of cancer cells (24) We carried out RT-PCR analysis to evaluate genetic characteristics of SP and MP cells derived from ACHN and RenCa cells (Fig. 2C).…”
Section: Isolation and Analysis Of Rcc Stem-like Population From Humamentioning
confidence: 99%
“…In recent years, it has been shown that SP cells exist in various types of tumours, including the CRC (Haraguchi et al, 2006;Sussman et al, 2007;Burkert et al, 2008). However, it is important to note that these studies are conflicting and stringent functional characterisation of SP cells in CRC is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are also some studies report that SP cells have not been shown to possess stem cell properties (Triel et al, 2004;Burkert et al, 2008;Lichtenauer et al, 2008;Broadley et al, 2011). There have been few studies directly comparing SP and Non-SP in CRC and yielding inconsistent results (Haraguchi et al, 2006;Burkert et al, 2008). These studies need to be confirmed using more cancer cell lines and especially primary tumour to have a better understanding of the involvement of SP in CRC.…”
mentioning
confidence: 99%